Blueprint for the 21st century online learning environment in stem education through a systematic review and qualitative synthesis - Meylani, Ruşen (Edelweiss Applied Science and Technology, 2024)
This study explores the critical role of STEM education in equipping students for the challenges of the 21st century and examines the effectiveness of Online Learning Environments (OLEs) in delivering such education. The purpose of this research is to identify the essential characteristics of effective OLEs and provide a comprehensive blueprint for their development. Utilizing a systematic review and qualitative synthesis of 228 peer-reviewed articles published between 2000 and 2023, the study adopts a rigorous methodological approach following PRISMA guidelines to analyze key trends, themes, and actionable insights. Findings reveal 46 essential features of optimal OLEs, categorized into ten themes: future-proofing, brain-based approaches, diverse learning mechanisms, high-fidelity implementation, instructional design perspectives, advanced technologies, online learning objects, pedagogical approaches, psychological considerations, and usability factors. These findings emphasize the integration of innovative technologies and pedagogical strategies to create engaging, inclusive, and adaptive learning environments tailored to diverse learner needs. The study concludes with a comprehensive blueprint designed to guide educators, policymakers, and technology developers in creating OLEs that enhance engagement and learning outcomes in STEM education. Practical implications include actionable recommendations for integrating emerging technologies, fostering professional development, and addressing accessibility challenges to democratize STEM education and prepare learners for the digital economy.